Calcium-sensing receptor promotes calcium oxalate crystal adhesion and renal injury in Wistar rats by promoting ROS production and subsequent regulation of PS ectropion, OPN, KIM-1, and ERK expression. Issue 1 (1st January 2021) - Li, Xiaoran; Chen, Siyu; Feng, Demei; Fu, Yuqiang; Wu, Huang; Lu, Jianzhong; Bao, Junsheng
Abstract: Objectives: To explore the mechanism of calcium-sensing receptors (CaSRs) during the development of nephrolithiasis. Materials and methods: Wistar rats were treated with ethylene glycol to induce calcium oxalate crystallization, and gadolinium chloride (GdCl3, an agonist of CaSR) and NPS 2390 (an antagonist of CaSR) were added. Oxidative stress (OS) and calcium oxalate crystals in the kidney were observed. CaSR expression and the expression of extracellular signal-regulated protein kinase (ERK), OPN, and KIM-1 were determined by western blotting. In addition, renal tubular epithelial cells were isolated from the kidney to observe phosphatidylserine (PS) ectropion using flow cytometric analysis. Various biochemical parameters were assessed in serum and urine at the end of the experiment. Results: Calcium oxalate increased OS, crystal adhesion, PS ectropion, and the expression of CaSR and ERK, OPN, and KIM-1 in vivo . In addition, lower levels of urine citrate as well as increased serum creatinine and urea levels were observed after treatment with calcium oxalate ( p  < .05). Compared with calcium oxalate treatment alone, the above deleterious changes were further significantly confirmed by GdCl3 but were reversed by NPS-2390. However, urine calcium excretion was decreased after ethylene glycol treatment but was significantly reduced by NPS 2390 and increased by GdCl3 ( p  < .05). Conclusions: The results suggest that CaSR might play significant roles in the induction of nephrolithiasis in rats by regulating reactive oxygen species (ROS) and PS ectropion and the composition of urine, OPN, KIM-1, and ERK expression.